Peligrosidad de Botrytis cinerea Pers. en siembras adelantadas de garbanzo en Extremadura - Del Moral, J.=700 1 Chica, V.; Gallego, M.; Casado, D.
(Es, En)
Ilus., 14 ref.
Keywords: GARBANZO; BOTRYTIS CINEREA; ENFERMEDDAES FUNGOSAS; SIEMBRA; CONTROL QUIMICO; PROCIMIDONA; ESPAÑA